Shedding light on sporopollenin chemistry, with reference to UV reconstructions - Jardine, Phillip E.; Abernethy, Feargus A.J.; Lomax, Barry H.; Gosling, William D.; Fraser, Wesley T. (Elsevier, 2017)
Sporopollenin, which forms the outer wall of pollen and spores, contains a chemical signature of ultraviolet-B flux via concentrations of UV-B absorbing compounds (UACs), providing a proxy for reconstructing UV irradiance through time. Although Fourier transform infrared (FTIR) spectroscopy provides an efficient means of measuring UAC concentrations, nitrogen-containing compounds have the potential to bias the aromatic and hydroxyl bands used to quantify and standardise UAC abundances. Here, we explore the presence and possible influence of nitrogen in UV reconstruction via an FTIR study of Lycopodium spores from a natural shading gradient. We show that the UV-sensitive aromatic peak at 1510 cm‾¹ is clearly distinguishable from the amide II peak at 1550 cm‾¹, and the decrease in aromatic content with increased shading can be reconstructed using standardisation approaches that do not rely on the 3300 cm‾¹ hydroxyl band. Isolation of the sporopollenin results in the loss of nitrogen-related peaks from the FTIR spectra, while the aromatic gradient remains. This confirms the lack of nitrogen in sporopollenin and its limited potential for impacting on palaeo-UV reconstructions. FTIR is therefore an appropriate tool for quantifying UACs in spores and pollen, and information on UV flux should be obtainable from fossil or processed samples.